(untitled) (The Review of Diabetic Studies, 2024)
Health informatics and medical coding are very important for modern healthcare systems. They are the basis for healthcare quality, clinical decision-making, and data accuracy. Standardizing medical coding makes sure that diagnoses, procedures, and healthcare services are recorded in a way that is both accurate and consistent. This, in turn, makes it easier to talk to each other, get paid, and look at health data. Health informatics, on the other hand, combines healthcare, IT, and data science to improve patient care, make clinical workflows more efficient, and support decision-making based on evidence. This review examines the fundamental concepts, historical development, and principal functions of health informatics and medical coding to elucidate their interrelated roles within healthcare systems. Some of the topics covered are electronic health records, clinical decision support systems, code classification systems, health information security, and data analytics. The evaluation also looks at professional skills, ethical issues, and current problems like data interoperability, cybersecurity threats, and the need for more workers. New technologies like AI, automation, and big data analytics are also talked about as revolutionary forces that will change the future of healthcare. Healthcare companies that use health informatics and medical coding together can improve their operations, make patient care safer, and set up long-term, data-driven healthcare systems. This review emphasizes the importance of multidisciplinary collaboration and continuous education and training to meet the evolving demands of modern healthcare systems.